Development of oil sorbent from pineapple leaf fibers using succinic anhydride modification in ionic liquid - Katinonkul, Watcharee; Onjun, Orasa (Bulletin of Applied Sciences, 2022)
Pineapple leaf fiber (PALF)was a natural fiber source for development of oil sorbent using succinic anhydride modification in ionic liquid in order to modify the hydrophilic hydroxyl group in cellulose structure by replacing with hydrophobic functional group via acetylation reaction. The ionic liquid in this study was 1-butyl-3-methylimidazolium chloride was used as ionic liquid. The effects of reaction time, temperature, molar ratio of succinic anhydride to cellulose, and N-bromosuccinimide (NBS) as a catalyst were studied. It was found that the optimal reaction condition at reaction time 120 min, temperature 120 °C, a ratio of succinic anhydride and cellulose 6:1 (m:m), 6% NBS and soaking in media after completed reaction for 15 hours, providing the maximum oil absorption capacity at 29.2 g/g while the untreated PALF had oil absorption capacity at 11.3 g/g.The characterization analysis of the modified PALF was performed using fourier transform infrared spectro- meter (FT-IR), thermogravimetric analysis (TGA), x-ray diffractometer (XRD), and scanning electron microscopy (SEM).